2020
DOI: 10.1177/0018578720928262
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Rosuvastatin and Ticagrelor Leading to Rhabdomyolysis: A Case Report and Narrative Review

Abstract: Objective: Drug interactions are a common cause of morbidity and mortality and may require prompt discontinuation of therapeutic regimens due to harmful side effects. Patients with acute coronary syndromes are likely to be prescribed multiple medications that are metabolized through the cytochrome P450 system, increasing the probability for drug interaction. Atorvastatin and simvastatin are both well known to interact with the oral P2Y12 agent ticagrelor. The purpose of this paper is to describe the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…Administration of RSV was reported to cause proximal tubule damage and renal toxicity in rats [ 35 ] and acute interstitial nephritis in humans [ 36 ]. In addition, RSV caused renal damage associated with severe rhabdomyolysis, whether RSV was given alone [ 37 , 38 , 39 ], or in combination with colchicine [ 40 ], ticagrelor [ 41 ], or cocaine and heroin [ 42 ]. Despite that the results of the current study suggested that RSV had protective effects against DN, long-term follow-up studies are needed to confirm whether RSV improves DN or just delays its progress.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of RSV was reported to cause proximal tubule damage and renal toxicity in rats [ 35 ] and acute interstitial nephritis in humans [ 36 ]. In addition, RSV caused renal damage associated with severe rhabdomyolysis, whether RSV was given alone [ 37 , 38 , 39 ], or in combination with colchicine [ 40 ], ticagrelor [ 41 ], or cocaine and heroin [ 42 ]. Despite that the results of the current study suggested that RSV had protective effects against DN, long-term follow-up studies are needed to confirm whether RSV improves DN or just delays its progress.…”
Section: Discussionmentioning
confidence: 99%
“…Несмотря на очевидные преимущества комбинированной антиагрегантной и гиполипидемической терапии, возможное взаимодействие между статинами и тикагрелором может привести к миопатии и рабдомиолизу [8][9][10][11][12][13][14][15][16][17]. В обзорной статье P.T.…”
Section: Rosuvastatin Ticagrelor and The Risk Of Rhabdomyolysisunclassified
“…В настоящее время имеется ряд публикаций о клинических случаях рабдомиолиза у пациентов, одновременно принимающих после ЧКВ широко используемые статины (розувастатин, аторвастатин, симвастатин) и антитромбоцитарный препарат тикагрелор [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Although usually well‐tolerated, rosuvastatin can cause muscle symptoms of varying severity, especially at higher doses 1 . Previously published case reports have suggested that concomitant use of rosuvastatin and the platelet‐inhibitor ticagrelor may have led to severe, even fatal, cases of rosuvastatin‐induced rhabdomyolysis 2–13 . Because the risk of rosuvastatin‐induced myotoxicity is concentration‐dependent, the rhabdomyolysis cases suggest a potential pharmacokinetic drug–drug interaction between ticagrelor and rosuvastatin.…”
mentioning
confidence: 99%